KORUPSI DAN PERTUMBUHAN EKONOMI NEGARA-NEGARA ASIA PASIFIK - Sri Nawatmi (Jurnal Bisnis dan Ekonomi, 2014)
The research want to analysis about corruption and economic growth. The method of analysis use pooling data. Number ofcross-section data are14 countries and times-series data are nine years. The best model obtained from redundant fixedeffect test, correlated random effects-Hausman test and technical consideration. The model is fixed effect model. Based onregression output, corruption havepositif significant to 12 Asia Pasific countries economic growth. So, corruption are notbecome a grease of wheel for that countries. If corruption (corruption perception index/CPI) increase, economic growthincrease too. While, another variables like FDI, and government budget for healthy have positive significant to theeconomic growth. Actually, onlyfivecountries in which the CPI variable significantly to economic growth. Two countrieshave positif significant (Japan and Korea) and anotherhave negatif significant(Brunei Darussalam,Timor Leste, andKamboja).Key words: CPI, economics growth, pooling data, none, fixed, and grease of wheel